Modeling the Thermally Stimulated Evolution of Hydrogen from Ti, Zr, Pd, and Ni; Bulletin of the Russian Academy of Sciences: Physics; Vol. 86, iss. 5 - Zhang Hongru; Nikitenkov N. N. Nikolai Nikolaevich; Sypchenko V. S. Vladimir Sergeevich; Ma Syaole; Tyurin Yu. I. Yuri Ivanovich (2022, 2022)
Title screen